Prevalence of anemia on chronic kidney disease and its influenced factors in Sanglah General Hospital 2015-2017, Bali - Rubahshini Gunaseelan; I Wayan Surudarma; Desak Made Wihandani; I Wayan Gede Sutadarma (Intisari Sains Medis, 2020)
Background: Anemia is the most common disease among chronic kidney disease (CKD) patients. Its prevalence increased gradually as kidney function decreased. Globally, it affects 1.62 billion people, which corresponds to 24.8% of the population.Aim: To determine the prevalence of anemia on CKD and its influenced factors at Sanglah Hospital, Bali.Method: This was a descriptive design study conducted in Sanglah General Hospital, Denpasar, Bali from 2015 until 2017. Medical records of the patients became the secondary data for this research.Result: From 2015 to 2017, there were 384 cases of CKD and 95 were anemic in the hospital. The prevalence of this case was 24.7 %. The age group of 51 - 60 years had the highest case. The males majorly dominated anemia on CKD. Anemia in stage V of CKD patients was the highest, and it increased more significant as the stages worsen, and diabetes was the leading underlying disease among anemia in CKD patients followed by CVD and glomerulonephritis. The hemoglobin level mean and glomerular filtration rate was lower than the normal one.